Approaches to the Implementation of a Teacher’s Professional Standard: Labor Actions and Systemic Meanings - Uskova S.A. (Психолого-педагогические исследования)
The article presents the analysis of the introduction of the professional standard of the teacher (the Standard), and analyzed the risks the formal implementation of the requirements of the Standard situation when the teacher can not organize and build relationships in the framework of functional maps of the profession and driving its operations to implement the desired work functions that does not allow the execution of one of the main functions of the Standard - improve the effectiveness of the educational process. The author presents a theoretical model of modern educational process; the proposed mechanism is a system implementation of the Standard proved the importance of the consideration of the necessary skills and knowledge as the employment action; it shows the variability of implementation of the Standard in accordance with emerging problems in the professional activity of the teacher, the peculiarities of the system of implementation of the Standard by the example of one work function: teaching activities for the implementation of the programmes of primary General education. Testing showed the importance of using the system implementation of the Standard as methodological tools in the process of thinking as a teacher this document. An empirical test of performance was carried out on the basis of an analysis of the final work of 98 students of continuing education courses (primary school teachers). 78% of teachers designed EP, identified the main\ components in it and correlated them with the main labor functions. 83% of teachers switched from formal adherence to the standard to the conscious design of the study program.